Work psychology trends: is theory the best practise? - Đurišić-Bojanović, Mirosava Miličko; Maksić, Slavica (Psihološka istraživanja, 2021)
The paper deals with the relationship between academic, applied and practical knowledge in the field of applied psychology, which has the potential to contribute to economic and social development. The aim of this analysis is to give an initial insight into the dominant topics and social relevance of research activities in the field of work psychology in Serbia in the period of significant social change (1995-2019). The material for the analysis consisted of abstracts of papers in the field of work psychology, which were presented at two leading national conferences - Empirical Research in Psychology and the Meeting of Psychologists of Serbia (N = 657). The authors used a thematic analytical procedure for the construction of a code system which defined the criteria for collecting relevant data. Exploratory sequential design and comparative longitudinal analysis were used for data processing. The obtained results indicate the emergence of new topics and areas, as well as the existence of a link between significant social changes and research activities in the field of work psychology in this period. The results of the analysis are also considered from the perspective of newer models of strategic planning and social development. Some elements of the new paradigm of positive human resource development practice are highlighted. The paper discusses the broader theoretical-methodological and practical implications of the findings for the work psychology.